In vivo P-glycoprotein function before and after epilepsy surgery - Bauer, Martin (Lippincott Williams & Wilkins, 2014)
OBJECTIVES: To study the functional activity of the multidrug efflux transporter P-glycoprotein (Pgp) at the blood-brain barrier of patients with temporal lobe epilepsy using (R)-[(11)C]verapamil (VPM)-PET before and after temporal lobe surgery to assess whether postoperative changes in seizure frequency and antiepileptic drug load are associated with changes in Pgp function. METHODS: Seven patients with drug-resistant temporal lobe epilepsy underwent VPM-PET scans pre- and postsurgery. Patients were followed up for a median of 6 years (range 4–7) after surgery. Pgp immunoreactivity in surgically resected hippocampal specimens was determined with immunohistochemistry. RESULTS: Optimal surgical outcome, defined as seizure freedom and withdrawal of antiepileptic drugs, was associated with higher temporal lobe Pgp function before surgery, higher Pgp-positive staining in surgically resected hippocampal specimens, and reduction in global Pgp function postoperatively, compared with nonoptimal surgery outcome. CONCLUSIONS: The data from our pilot study suggest that Pgp overactivity in epilepsy is dynamic, and complete seizure control and elimination of antiepileptic medication is associated with reversal of overactivity, although these findings will require confirmation in a larger patient cohort.